Modeling Congenital Hyperinsulinism with ABCC8-Deficient Human Embryonic Stem Cells Generated by CRISPR/Cas9 - Dongsheng Guo (Nature Portfolio, 2017)
Abstract Congenital hyperinsulinism (CHI) is a rare genetic disorder characterized by excess insulin secretion, which results in hypoglycemia. Mutation of sulfonylurea receptor 1 (SUR1), encoded by the ABCC8 gene, is the main cause of CHI. Here, we captured the phenotype of excess insulin secretion through pancreatic differentiation of ABCC8-deficient stem cells generated by the CRISPR/Cas9 system. ABCC8-deficient insulin-producing cells secreted higher insulin than their wild-type counterparts, and the excess insulin secretion was rescued by nifedipine, octreotide and nicorandil. Further, we tested the role of SUR1 in response to different potassium levels and found that dysfunction of SUR1 decreased the insulin secretion rate in low and high potassium environments. Hence, pancreatic differentiation of ABCC8-deficient cells recapitulated the CHI disease phenotype in vitro, which represents an attractive model to further elucidate the function of SUR1 and to develop and screen for novel therapeutic drugs.